2016
DOI: 10.1111/gec3.12279
|View full text |Cite
|
Sign up to set email alerts
|

Resilience, Political Ecology, and Power: Convergences, Divergences, and the Potential for a Postanarchist Geographical Imagination

Abstract: Over the past three decades, resilience has emerged as an ecological concept that has transformed the way international development is conceptualized. However, it is only recently that the topic has been approached within the geography literature. In this article, I trace the linkages between resilience as an ecological concept and an emerging framework in political geography, its relationship to the field of political ecology, and the potential of a postanarchist geography in bridging the extant gap between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 52 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…This paper aimed to address this limitation and showed that Bangkok's flood resilience policy is framed to prioritize economic growth and competitiveness with little focus on wider societal outcomes, especially at the community level. This result is in line with the theoretical argument in resilience literature arguing that an uncritical adoption of the resilience concept could prioritize economic interests, which might leave vulnerable populations behind (Davoudi, 2012;Cannon & Müller-Mahn, 2010;White & O'Hare, 2014;Marks, 2015;Mullenite, 2016). In addition, our results showed that the dominant economic growth frame is currently being challenged by the outsiders, who were not involved in the development of the resilience policy.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This paper aimed to address this limitation and showed that Bangkok's flood resilience policy is framed to prioritize economic growth and competitiveness with little focus on wider societal outcomes, especially at the community level. This result is in line with the theoretical argument in resilience literature arguing that an uncritical adoption of the resilience concept could prioritize economic interests, which might leave vulnerable populations behind (Davoudi, 2012;Cannon & Müller-Mahn, 2010;White & O'Hare, 2014;Marks, 2015;Mullenite, 2016). In addition, our results showed that the dominant economic growth frame is currently being challenged by the outsiders, who were not involved in the development of the resilience policy.…”
Section: Discussionsupporting
confidence: 90%
“…The focus on structural flood protection, particularly in economic significant areas, could lead to resilience policy promoting economic growth and competitiveness of a city (White & O'Hare, 2014). A resilience strategy anticipating mainly economic development outcomes is therefore by some scholars seen as an exclusionary process for the dominant economic interest, which is consistent with the neoliberal agenda (Mullenite, 2016;Shaw, 2012aShaw, , 2012b. Although economic development is highly relevant, especially for developing countries, several authors have argued that structural flood protection for economically significant regions could in turn transfer flood risks to other, disadvantaged communities (Davoudi, 2012;Marks, 2015;Vale, 2014).…”
Section: Outcomementioning
confidence: 81%
See 2 more Smart Citations
“…All sensitive and relational developments are contingent on environments, and on the social bonds created. Insurrectionary political ecology complements resilience research conceived as resistance to domination (Mullenite 2016) that "generates new forms of life" (Wakefield 2017: 13), as opposed to normalizing the political economy of exploitation. Fukuoka and insurrectionary anarchism can provide pathways of resilience for considering how to politically and ecologically organize with minimal effort, maintain low-logistical overhead and remain evasive.…”
Section: The Problem Of Organization: Counter-hegemony Versus Viral Smentioning
confidence: 99%